Polymorphous Low-Grade Adenocarcinoma - Shubhangi Mhaske; T Raju Ragavendra; Sandeep S Gupta; Kavitha P Kamath; Anil Ghom (Wolters Kluwer Medknow Publications, 2010)
Polymorphous low-grade adenocarcinoma (PLGA) is a rare, malignant salivary gland tumor commonly affecting the minor salivary glands, histologically showing morphological diversity and a low metastatic potential. Hereby reporting a case of PLGA in a 58-year-old male patient showing involvement of antral floor.